EFL LEARNERS’ ABILITY IN USING DISCOURSE MARKERS TO BUILD COHERENCE IN THE WRITING - Ulin Ni'mah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The study aims to investigate how EFL learners apply Discourse Markers (DMs) to make their writing coherent. This is a descriptive study conducted at UIN Maulana Malik Ibrahim Malang by observing essays written by Biology students learning English in semester IV. The researcher analyzed 52 DMs and how the students apply them in 28 essays. The findings of the study show that the participants use 21 different DMs in 148 occurrences, and use several DMs inappropriately in 68 occurrences. There are some problems found in the use of DMs such as mistranslation, overuse, surface logic, misinterpretation, and misplace. The conclusion of the study reveals that learners have already applied DMs in their texts to build coherence but some are used inappropriately. Therefore, the researcher suggests that materials about what types of DMs and how to apply DMs should be given in the classroom